Analysis of Value Chain of Cow Milk: The Case of Itang Special Woreda, Gambella, Ethiopia - Gagabo, Sisay Yohannes; Chika, Kulong Wechtuor; Kuse, Kenenisa Abdisa; Bora, Bereket Bekele (International Journal of Forest, Animal and Fisheries Research, 2024)
Ethiopia has a long and rich history of dairy farming, which was mostly carried out by small and marginal farmers who raised cattle, camels, goats, and sheep, among other species, for milk. Finding the Itang Special Woreda cow milk value chain is the study's main goal. In order to gather primary data, 204 smallholder dairy farmer households were randomly selected, and the market concentration ratio was calculated using 20 traders. Descriptive statistics, econometric models, and rank analysis were used to achieve the above specified goals. Out of all the participants in the milk value chain, producers, cafés, hotels, and dairy cooperatives had the largest gross marketing margins, accounting for 100% of the consumer price in channels I and II, 55% in channels III and V, and 25.5% in channels V. The number of children under five, the number of milking cows owned, the amount of money from non-dairy sources, the frequency of extension service contacts, the amount of milk produced each day, and the availability of market information were found to have an impact on smallholders' involvement in the milk market. Numerous obstacles also limited the amount of milk produced and marketed. The poll claims that general health issues, sickness, predators, and a lack of veterinary care are plaguing farmers. In order to address the issue of milk perishability, the researchers recommended the host community and organization to construct an agro milk processor, renovate the dairy cooperative in the study region, and restructure the current conventional marketing to lower the transaction and cost of milk marketing.